The paternal genetic structure of Jingpo and Dai in southwest China. (3rd April 2019) - Xu, Bingying; Guo, Jianxin; Huang, Ying; Chen, Xueyun; Deng, Xiaohua; Wang, Chuan-Chao
Abstract: Yunnan province harbours substantial genetic, cultural and linguistic diversity, with the largest number of Aborigines in China, but the relationship among these Aborigines remains enigmatic. This study genotyped 45 Y chromosomal single nucleotide polymorphisms (SNPs) of 500 males from two aboriginal cross-border populations, Jingpo and Dai, from Dehong, Yunnan. It is reported that Haplogroup O2a2b1a1-M117 is the dominant lineage in both Jingpo and Dai. The Jingpo people show affinity with Tibeto-Burman speaking populations with a relatively high frequency of Haplogroup D-M174, and the Dai people are generally genetically similar with Tai-Kadai speaking populations with high frequencies of Haplogroup O1a-M119 and O1b1a1a-M95, which is consistent with their language classification.